A REVIEW OF EDUCATIONAL MANAGEMENT, IMPLEMENTATION OF LEARNING ASPECTS AND BOARDING BOARDING COOPERATIONS - Aep Tata Suryana; Rifki Rifaldi; Rizqi Fauzi (JPUS: Jurnal Pendidikan Untuk Semua, 2026)
Islamic boarding schools in Indonesia have an important role in educating students, no only in the field of religion, but also in developing skills practical and relevant to the needs of the times. This paper aims to explore how cooperatives can be implemented in education in Islamic boarding schools and their impact on the skills and character of students. This research was conducted using a qualitative approach, which examines various things literature and case studies regarding cooperatives in Islamic boarding schools. Hence, paper It recommends that Islamic boarding schools increase collaboration with cooperatives and developing a more relevant curriculum to help students become better prepared to face the world of work and life in society.